PRAKTIK PEMBELAJARAN TEKS PROSEDUR DENGAN MEMASAK MAKANAN DALAM MENINGKATKAN KARAKTER MANDIRI DAN KREATIF PADA SISWA SD - Miko Fitri Ana; Ach Barizi; Mardiana Anjani Alamsyah; Lailatul Hidayati; Daroe Iswatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the learning of procedure texts using food cooking practice methods in improving independent and creative characters in elementary school students and analyze the factors that influence it. Practice-based learning, especially through cooking activities, is expected to provide direct experience in enriching students' understanding of procedure text, as well as developing life skills such as independence and creativity. This study used a qualitative approach with observation, interview, and documentation methods for 25 students of grade 5 at SD Muhammadiyah 29 Surabaya. The results showed that students experienced an increase in independence by 60% and creativity by 50%. The factors that influence the improvement of independent and creative characters in learning cooking practices come from individuals and inadequate resources.